Ragnar Nurkse and the international financial architecture - Barry Eichengreen (Baltic Journal of Economics, 2018)
This lecture discusses the work by the Estonian economist Ragnar Nurkse (1907-1959). It focuses on the early Nurkse, who was concerned with exchange rates, capital flows and what today we call the international financial architecture. It asks how many of the conclusions of International Currency Experience [Nurkse, R. (1944). International Currency Experience. Geneva: League of Nations.] survive. How many of Nurkse's points about the interwar gold standard are confirmed by subsequent scholarship? How many of his points are still relevant to the international monetary problems of today?
Keywords: F33; F42; N20; 330; International finance; fixed exchange rate; financial crises; Internationales Finanzsystem; Ökonomische Ideengeschichte